The Model of Decision Making for The Formulation of Integrative Islamic Boarding School Curriculum (Study of Response to KMA 183 and KMA 184 2019) - Marjuni (Future Science, 2021)
The purpose of this research is to explain that the support system makes decisions prepared by the principle of madrasas and the implementation of integrative curriculum development, how the integrative curriculum is created using a particular model, and the model of curriculum outcomes such as those prepared by the principle. The background of this study resulted in the phenomenon of the difficulty of madrasas principle in the boarding school environment to compile an integrated curriculum structure based on KMA 183 and KMA 184. This study used a qualitative method using phenomenology, data obtained by interviews in, studios, and direct observation. This study found (1) Decision Support System Concepts based on the principle of Madrasa Aliyah Wali Songo Dormitory Sons and Madrasa Aliyah Wali Songo Dormitory Girls are separate instruments made by humans assisted by systems made by computers that function as miners, processors, responders, and decision-makers based on needs and goals. (2) Preparation of an integrative curriculum is carried out with a dynamic and statistical model at the same time because the issue of expenditure will not be handled properly only on the statistical model. The integrated curriculum model according to Robert D. Speech was taken to solve complicated problems that occurred and ended with the formalization of decisions to ensure the validity of curriculum constructs and the legitimacy of decisions. (3) Integrated madrasa curriculum formulated by the Madrasa Aliyah Wali Songo Dormitory Sons and the Madrasa Aliyah Wali Songo Dormitory Girls is the Independent Curriculum Transdisciplinary (ICT).